The fresh politics reader : making current events and public affairs relevant to young Americans - Buley, Taylor W. (Silver Lake, 2006)
Young people aren't apathetic about politics; but they dislike cynicism. They like small government. This book draws from the web site fresh politics to give one perspective on what young Americans want and expect from politics and government. The author leads the discussion, and other bright young thinkers have their say. These young people understand that school, work, money and life are going to be less structured for them. They also understand that political sacred cows--abortion, Social Security and health insurance--may become hamburger during their lives. In The Fresh Politics Reader, they talk about relevant issues in a more detailed way than they did previous generations.